Experimental Values and Correlations of Some Thermal Properties of Fresh and Osmotically Dehydrated Stone Fruit - Rodriguez, Anabel (2014)
Nectarines, plums and peaches were dehydrated with osmotic solutions (glucose at 60°Brix or sorbitol at 60°Brix) at temperature of 35ºC for scheduled periods (0.5, 1, 2, 4, 6, 8 h). Thermal properties of fresh and osmotically dehydrated fruits were measured by DSC where samples were heated from –40ºC to 40ºC at a rate of 2ºC min–1. In this work, we obtained experimental data on the variation of water content and soluble solids during the osmotic dehydration of nectarines, peaches and plums in solutions of glucose or sorbitol; experimental data for enthalpy of fresh and osmotically dehydrated nectarines, plums and peaches as a function of temperature and type of osmotic solute; correlations for initial freezing temperature of osmotically dehydrated stone fruits as a function of water content and type of dehydrating solute and correlations between heat capacity or enthalpy and temperature for some fresh and osmotically dehydrated stone fruits.